Educação Sonora através da programação sônica: o desenvolvimento da criatividade e escuta mediado por composição algorítmica - Santos, João Victor Miranda Leão dos (2023)
Murray Schafer, a contemporary music educator, drew attention to the fact that creation is often not the main focus of music classes. In the context of elementary schools in the state of Ceará (Brazil), it is not only uncommon for creativity to receive the proper attention, but there are also traditional approaches that mainly focus on Music History, Music Theory, and/or score reading. Furthermore, it is rare for elementary school music students to have digital tools for composition during the teaching-learning process. Seymour Papert, the creator of Constructionism, stated that the best way to learn is through creative processes and that computer programming is an excellent tool for translating students' abstract thinking into something concrete, stimulating creativity and logical thinking. The aim of this study was to understand how an approach based on the principles of Sound Education and Constructionism can stimulate creativity and listening skills of secondary school students. To achieve this, the participants were challenged to create soundscapes through computer programming. Musical composition mediated by programming has been the subject of recent studies, although they still represent a small number. Using a triangular approach, the development of creativity and listening skills was observed in five subjects. All the evidence pointed to a significant stimulus for the development of creativity and expanded, sensitive, and conscious listening. However, feedback from participants through group discussion highlighted aspects that could be improved in future practices. It was concluded that the creation of soundscapes mediated by sonic coding (or algorithmic composition), under a constructionist approach, stimulates the development of both skills.